Professional and educational orientations of final-year students at regional university (based on empirical research) - E. N. Sharova; D. V. Maleus (Вестник университета, 2025)
The issue of incompleteness of the professional self-determination processes, characteristic of modern youth in general, has been studied. The emphasis has been placed on the institutional and structural conditions that determine the opportunities and limitations for successful professional socialization of young people in the context of specific territories. In the conditions of the Murmansk Region, the significant factors are demographic decline and personnel hunger, which determined the public demand for population retention and the quality of life improvement. The state of professional and educational orientations of the regional student population is a special research issue in the context of regional comprehensive development tasks realization. The analysis is based on the results of sociological research conducted in 2024 by online survey method among final-year students of regional universities in the Murmansk Region (477 people). The following main trends in the students’ professional and educational orientations have been revealed: a broad request for continuing education outside the region in a significant group of respondents (mainly those who receive secondary vocational education), fairly high rates of loyalty to the received direction of training/specialty, and active involvement in secondary employment in the process of education. The obtained results have applied value within the framework of the regional system of vocational education activities to retain the internal flow of students in the transition between training levels and to build further educational and professional trajectory of graduates.